Semiotic Analysis of The Logo and Sign Posts as Found in PT KAI Medan 2024 - Lasma Duma Lestari Hutauruk; Sondang Manik; Rony Arahta Sembiring (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This research focuses on a semiotic analysis of the logo and directional signs at the PT Kereta Api Indonesia (KAI) Medan Station. Utilizing Peirce's theory, this study identifies nine semiotic sign elements emerging from the analysis, with symbols dominating as the most frequently occurring element. The logo of PT KAI Medan, characterized by the use of dark blue color and a line crossing the letter "A," symbolically represents stability, professionalism, and reliability of the company, while directional signs within the company's environment are strategically positioned to provide clear information to station users. This research provides a profound understanding of the use of semiotic signs in assisting station users' navigation and offers a foundation for further research on the effectiveness of semiotic sign usage in the context of public transportation and its impact on user experience.